Millennial Santri Business Workshop: Empowering Tanwirut Thullab Islamic Boarding School Students to Diversify the Potential of Processed Dragon Fruit Products - Wicaksono, Iwan; Sutarto; Indrawati (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2023)
A Santriwati, of course, does not rule out the opportunity to be able to start a business to maximize the potential of dragon fruit agricultural products. The aim of empowerment is to form a Millennial Santri Business Workshop at the Tanwirut Thullab Islamic Boarding School, encouraging understanding of the potential of dragon fruit, building an entrepreneurial spirit, and the process of making processed dragon fruit products. The situation analysis indicated that problems were found, including: the decline in selling prices at the peak of the dragon fruit harvest, the poverty level of female students when they left the boarding school, and a lack of understanding of the potential of Sambirejo Village. The empowerment participants included 38 female students aged 17 - 18 years and who were about to complete their education. The approach used during the process of implementing this empowerment is an approach that includes: team formation, formulating goals, gathering stakeholders, gathering needs, determining problem priority analysis, preparation, implementation, mentoring, review and evaluation, determining new needs and targets. As a result of empowering Santriwati, they gain understanding and skills to make processed Dragon Fruit Pudding, Jam and Jenang Grendul products as entrepreneurial provisions. The response shown by Santriwati, 72% gave a very positive response and 18% gave a positive response regarding product understanding, entrepreneurial spirit and the product manufacturing process. The series of empowering Santriwati in the Millennial Santri Business Workshop to build an entrepreneurial spirit starts from the stage of selecting ingredients, composition and processing of processed products that have the potential to be produced and sold to consumers.